2018
DOI: 10.1016/j.nrl.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de deterioro cognitivo en España. Estudio Gómez de Caso en redes centinelas sanitarias

Abstract: Cognitive impairment is a frequent reason for consultations in primary care. Its prevalence is higher in women and increases exponentially with age. A number of sensitive, validated tools have been proven useful in screening for and confirming cognitive impairment. Using these tools in primary care settings enables early treatment of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 20 publications
0
10
0
8
Order By: Relevance
“…The highest prevalence rate of MCI was observed in people aged ≥85 years, in which almost 50% of those individuals within this age demographic will meet the criteria from MCI. 7 A population-based survey in Tai'an city showed an occurrence rate of MCI that is higher with empty-nest older adults from rural regions than those from urban areas. 4 Furthermore, some researchers have found that the living arrangements for emptynesters constitute a specific risk factor for MCI.…”
Section: Introductionmentioning
confidence: 99%
“…The highest prevalence rate of MCI was observed in people aged ≥85 years, in which almost 50% of those individuals within this age demographic will meet the criteria from MCI. 7 A population-based survey in Tai'an city showed an occurrence rate of MCI that is higher with empty-nest older adults from rural regions than those from urban areas. 4 Furthermore, some researchers have found that the living arrangements for emptynesters constitute a specific risk factor for MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Deterioro cognitivo, depresión y estrés asociados con enfermedades crónicas en adultos mayores, Cuenca 2014. Buenaño Barrionuevo Llaquelina Amanda cognitivo es baja con el 3.5%, en relación con estudios realizados en España que fue del 18.5% [4] y en México del 7.3% [5] Ninguna de las enfermedades en estudio fue un factor de riesgo para el deterioro cognitivo, este dato se correlaciona con el encontrado por Abambari y colaboradores en el mismo Centro [7]; en relación con la diabetes, Muñoz y colaboradores [13] concluyen su estudio citando que es una enfermedad que daña muchos órganos, aunque no se ha demostrado científicamente que el cerebro sea uno de ellos.…”
Section: En El Presente Estudio La Prevalencia De Deteriorounclassified
“…El deterioro cognitivo que puede llevar a la demencia, se presenta en el 1% de la población de 80-85% años y llega hasta un 20% en adultos mayores de más de 90 años [3], en España se ha detectado una prevalencia de 18.5% [4]; En México los indicadores de salud mental reportaron que el 17.6% presentó síntomas depresivos, 7.3% deterioro cognitivo y 7.9% demencia [5].…”
Section: Introductionunclassified
“…The overall prevalence of MCI in Spain is estimated to be around 18.5% of individuals aged over 65 years, and this figure is eight times higher in the group aged over 85 years (Alonso et al, 2018). It is most often seen as a reduced memory capacity and is usually accompanied by significant behavioral and emotional changes, such as depression, irritability, anxiety, apathy, and agitation (Gallagher, Fischer, & Iaboni, 2017; King, Cáceres, & Abdulkadir, 2018; Samy, Kamaruzzaman, Krishnaswamy, & Low, 2019).…”
Section: Introductionmentioning
confidence: 99%